2018
DOI: 10.1161/circresaha.117.311302
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Cell Therapy Studies in Heart Failure and Acute Myocardial Infarction

Abstract: Heart failure (HF) is one of the leading causes of death worldwide and has reached epidemic proportions in most industrialized nations. Despite major improvements in the treatment and management of the disease, the prognosis for patients with HF remains poor with approximately only half of patients surviving for 5 years or longer after diagnosis. The poor prognosis of HF patients is in part because of irreparable damage to cardiac tissue and concomitant maladaptive changes associated with the disease. Cell-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 55 publications
0
59
0
1
Order By: Relevance
“…Proper meta-analyses of SCI trials are essential for moving forward from multiple completed trials with varying results, to clinical application (Haidich, 2010;Ciccocioppo et al, 2018;Gyöngyösi et al, 2018;Shu et al, 2018;Sun et al, 2018;Yang et al, 2018). Weiss et al suggest that medical societies and associations play a proactive role in keeping clinicians informed and educating patients about approved interventions along with counselling by health care providers (Weiss et al, 2018).…”
Section: Role Of Medical Societies and Organisations: Keeping Clinicimentioning
confidence: 99%
“…Proper meta-analyses of SCI trials are essential for moving forward from multiple completed trials with varying results, to clinical application (Haidich, 2010;Ciccocioppo et al, 2018;Gyöngyösi et al, 2018;Shu et al, 2018;Sun et al, 2018;Yang et al, 2018). Weiss et al suggest that medical societies and associations play a proactive role in keeping clinicians informed and educating patients about approved interventions along with counselling by health care providers (Weiss et al, 2018).…”
Section: Role Of Medical Societies and Organisations: Keeping Clinicimentioning
confidence: 99%
“…On the other hand, despite the incontrovertible beneficial effects observed in patients with chronic heart failure using autologous and allogenic CSCs [ 54 ] and in patients with refractory angina using endothelial progenitor cells [ 55 ], clinical trials for myocardial regeneration remain still debated and controversial because the results are modest [ 56 ]. CSCs transplantation, as tested so far in humans, is not sufficient to promote an effective cardiac regeneration [ 57 ], and the low survival rate of transplanted cells further limits the therapeutic efficacy of cell therapy [ 57 ], coupled with the fact that CSCs could be rapidly removed from the body shortly after systemic injection.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the concept of cell-based therapies may have the potential to transform the treatment and prognosis of heart failure through regeneration or repair of injured cardiac tissue [3,4]. Most clinical trials have used bone marrow derived mononuclear cells (BMCd), which have demonstrated inconsistent and, overall, modest efficacy [5].…”
Section: Introductionmentioning
confidence: 99%